Black/Jewish imaginaries and children's literature: reading resistance and intersectionality in A Pickpocket's Tale. Issue 3 (3rd July 2019) - King, Nicole
ABSTRACT: In this essay I apply theories of intersectionality to A Pickpocket's Tale (2006), a young adult novel which imagines eighteenth-century Britishness, indenture, slavery, and Jewishness. I argue that the text represents feminist resistance and its limits as located within the shared social and physical spaces of Jewishness and blackness. My discussion of the novel's discourse of resistance focuses on scenes, characters and settings where Jewishness and blackness are defined and intersect. By focusing on its black/Jewish coalitional politics I conclude that A Pickpocket's Tale presents a politicised intersectional narrative of racial, gender and religious identity, both subversive and conservative.